A critical review of Microgrid adaptive protection techniques with distributed generation. (December 2021) - Kaur, Gurpreet; Prakash, Anupama; Rao, K. Uma
Highlights: The MG along with its benefits also causes various problems and challenges due to the DG interconnection. Out of the reviewed papers the Adaptive protection is emerging as the new and reliable solution for the MG protection. Therefore, designing a new MG adaptive protection scheme is key to proper operation and control of DS with DGs. Abstract : The main technical challenges in the emerging concept of the micro-grid (MG) and integration of sustainable energy resources in the Distribution System (DS) is the low fault current phenomena in the islanded mode of the MG operation and change in the network topologies with frequent DG connection and disconnection. The existing protection schemes require modification as they may fail to operate because of their inability to adapt to the changes due to the integration of Distributed Generator (DG). Various new protection schemes have been introduced by many researchers for this new concept of Microgrid (MG) that is not only adaptive to the changes in the levels of fault current and network topologies in both grid-connected and islanded modes but also intuitive enough to determine and clear the fault with minimum disturbances in the supply. This paper gives a brief review of the challenges associated with Microgrid protection and presents a critical review of the existing Microgrid protection schemes. The limitations of the existing adaptive protection schemes that need to be overcome to make adaptive protection scheme a viable solution are also presented.